2020
DOI: 10.1016/j.jsv.2019.115134
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for damage quantification using the dynamic response of a metallic beam under thermo-mechanical loads

Abstract: This paper investigates the interdependencies of crack depth and crack location on the dynamic response of a cantilever beam under thermo-mechanical loads. Temperature can influence the stiffness of the structure, thus, the change in stiffness can lead to variation in frequency, damping and amplitude response. These variations are used as key parameters to quantify damage of Aluminum 2024 specimen under thermo-mechanical loads. Experiments are performed on cantilever beams at non-heating (room temperature) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…This width initiated at the base of the given seeded crack and showed a more representative decrease in natural frequency due to real propagation. Theoretically, the amplitude should increase as the crack depth and temperature increase due to the reduction in the structural stiffness, as observed by the authors as shown in Figure 18 [31]. On the other hand, the amplitude discrepancy, illustrated in Figures 19 and 20, was observed for crack depth and temperature.…”
Section: Dynamic Responsementioning
confidence: 64%
See 2 more Smart Citations
“…This width initiated at the base of the given seeded crack and showed a more representative decrease in natural frequency due to real propagation. Theoretically, the amplitude should increase as the crack depth and temperature increase due to the reduction in the structural stiffness, as observed by the authors as shown in Figure 18 [31]. On the other hand, the amplitude discrepancy, illustrated in Figures 19 and 20, was observed for crack depth and temperature.…”
Section: Dynamic Responsementioning
confidence: 64%
“…The geometry of the model was imported from SolidWorks©. Behzad et al [31] re-arranged Equations (3)-(5), to have a comprehensive formula that can represent the crack depth and location with the material properties, as shown in Equation 7.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst this entire subject has been researched extensively, the challenge of synthesizing a stiff material with intrinsic self-healing capabilities remains a significant challenge. The fundamentals of damage mechanics are based on energy release during crack initiation and propagation [ 110 , 111 , 112 , 113 ]. The main actuation of the proposed self-healing capsules is based on strain energy release within the sub-surface.…”
Section: Potential Impacts Of Smart Self-healing 3d Printed Structmentioning
confidence: 99%
“…A variety of non-destructive techniques are used in the industry to inspect structural assets for damage detection and remedial action. A great deal of encouraging research is also taking place around using simple vibration tests and measurements of structural dynamic properties to infer the correct location and severity of damage in engineering structures [5][6][7][8][9][10][11][12][13][14][15][16]. The dynamic response of a structure can be used to measure the elastic properties of the constituent material [17].…”
Section: Introductionmentioning
confidence: 99%